THE ROLE OF TALENT MANAGEMENT, PROFESSIONAL COMPETENCY, TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE MEDIATED BY EMPLOYEE ENGAGEMENT - Aryono Prakoso; Saparuddin; Kazan Gunawan (Modern Scientific Technology, 2024)
This research is intended to analyze the influence of talent management, professional competence, and transformational leadership on employee performance mediated by employee engagement in BPK RI employees. The research method used is an explanatory survey which is a type of causality research that aims to obtain an explanation of the causal relationship between several concepts or variables. The objects of this research are aspects of talent management, professional competence, transformational leadership, employee engagement, and employee performance. The research subjects were 360 BPK RI employees. This research uses PLS-SEM because it aims to test the predictive relationship between constructs by seeing whether there is a relationship or influence between constructs. The research results show that talent management has a positive effect on employee performance, professional competence has a positive effect on employee performance, transformational leadership has a positive effect on employee performance, talent management has a positive effect on employee engagement, professional competence has a positive effect on employee engagement, transformational leadership has a positive effect on employees engagement, talent management influences employee performance through employee engagement, professional competence influences employee performance through employee engagement and transformational leadership influences employee performance through employee engagement